Synthesis of Certain 3-(Alkyl/Arylthioureido)-5-Alkylimino-4-Alkyl-1,2,4-Δ2-Thiadiazolines - Joshua, C.P.; Sheena, S. (Asian Journal of Chemistry, 2010)
Condensation of 5-alkylimino-3-amino-4-alkyl-1 ,2,4-Δ2 -thiadiazolines and alkyl/aryl isothiocyanates in a basic medium yields 3-( alkyl/aryl thioureido)-5-alkylimino-4-alkyl-1 ,2,4-Δ2 -thiadiazolines. Their structures have been established by chemical analysis and spectral data. The steric effects of alkyl or aryl groups do not affect the course of the reaction.